Knowledge Sharing Sebagai Sumber Inovasi dan Keunggulan Bersaing Pada Usaha Mikro Kecil dan Menengah (UMKM) Sektor Batik - Drs. M. Assegaf, MM -; Dra. Wasitowati, MM - (Conference In Business, Accounting, And Management (CBAM), 2015)
Small and medium batik sector are significantly contribution to econo mic development and the cultural  heritage,  but development are still many prob lems, especially  the  empowerment  of  internal   assets  so  it  has  an  impact  on  the development of innovation capability ann competitive advantage.  This study aims to examine the effect of knowledge sharing  process   to innovation capability and competitive  advantage   at    small  and  medium  batik  sector  in  Central   Java. Sampling methods using purposive sampling and data  analysis using the Partial Least  Square  (PLS).  The  research   results       that    knowledge  donataing   and knowledge collecting are significantly effect on innovation capability. Knowledge donating, knowledge collecting and innovation capability  are  significantly effect on the  competitive advantage.  Keywords: Knowledge collecting , Knowledge donating, Innovation capability